2020
DOI: 10.1186/s10020-019-0135-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of biomarkers in common chronic lung diseases by co-expression networks and drug-target interactions analysis

Abstract: Background: asthma, chronic obstructive pulmonary disease (COPD), and idiopathic pulmonary fibrosis (IPF) are three serious pulmonary diseases that contain common and unique characteristics. Therefore, the identification of biomarkers that differentiate these diseases is of importance for preventing misdiagnosis. In this regard, the present study aimed to identify the disorders at the early stages, based on lung transcriptomics data and drug-target interactions. Methods: To this end, the differentially express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 87 publications
1
33
0
1
Order By: Relevance
“…Some of the common gene targets like GADD45B needs further attention and characterization especially in the chronic lung diseases like COPD and IPF. Recent biomarker identification study indicated GADD45B in their list of genes that can be targeted in chronic diseases like asthma, IPF, and COPD (Maghsoudloo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the common gene targets like GADD45B needs further attention and characterization especially in the chronic lung diseases like COPD and IPF. Recent biomarker identification study indicated GADD45B in their list of genes that can be targeted in chronic diseases like asthma, IPF, and COPD (Maghsoudloo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Aging influences many chronic lung diseases, such as COPD, idiopathic pulmonary fibrosis (IPF), and asthma. Also chronic lung diseases like asthma and IPF share some of the common yet distinct features compared to COPD (Maghsoudloo et al, 2020). Environmental stress factors like smoking remains a common influencing factor for the disease progression in all these three cases.…”
Section: Introductionmentioning
confidence: 99%
“…Accompanied by the opposite direction of changes in DNAm between males and females at most of the identified CpGs in both cohorts, this suggests that DNAm may represent a mechanism underlying the well-established gender reversal in asthma prevalence across adolescence. 15,16 In addition, assessment of the biological relevance for 9 of the cases compared to controls, 52 and gene CCDC146 is also identified as one of the differentially expressed genes in relation to asthma, 53 although it is unclear whether such differentiation is different be- At most of the CpGs identified in IOWBC, consistent direction of interaction effects was found in ALSPAC. However, statistical significance was not observed at those CpG sites except for cg20891917.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the common gene targets like GADD45B needs further attention and characterization especially in the chronic lung diseases like COPD and IPF. Recent biomarker identification study indicated GADD45B i n their list of genes that can be targeted in chronic diseases like asthma, IPF and COPD 6 .…”
Section: Discussionmentioning
confidence: 99%